Emotional labor as emotional regulation: Italian adaptation and longitudinal validation of the scale among undergraduate nursing students. (January 2023) - Dal Santo, Letizia; Longhini, Jessica; Andela, Marie; Battistelli, Adalgisa; Galletta, Maura
Abstract: Aim: The aim of the present study is to perform a longitudinal Italian validation of the scale and to adapt it to the nursing education contest. Background: Research on emotional labor has shown that the roles played by surface acting and deep acting are still uncertain. To overcome this gap, scholars suggest observing emotional labor through the lens of the emotional regulation theory. Andela and her colleagues developed a fine grained instrument, which differentiates attentional deployment, cognitive re-evaluation and expressive suppression, emotional amplification and emotional dissonance. Design. To fulfill our aim, a longitudinal study was performed in an Italian University. Method. The adapted scale was administered to 168 nursing students across the three years of attendance in the course. Results. Our results confirm the five-factor structure, and the instrument shows good psychometrical properties. Conclusion. Having shown satisfactory psychometric properties, this scale can be considered a useful instrument to assess those emotional elements of clinical practice, which are important for the assurance of education quality to the under graduated nursing students.